Stability of clinical condition in mild cognitive impairment is related to cortical sources of alpha rhythms: An electroencephalographic study - Babiloni, Claudio (Hum Brain Mapp, 2010)
Previous evidence has shown that resting eyes‐closed cortical alpha rhythms are higher in amplitude in mild cognitive impairment (MCI) than Alzheimer's disease (AD) subjects (Babiloni et al. [2006a]: Human Brain Mapp 27:162–172; [2006b]: Clin Neurophysiol 117:252–268; [2006c]: Neuroimage 29:948–964; [2006d]: Ann Neurol 59:323–334; [2006e]: Clin Neurophysiol 117:1113–1129; [2006f]: Neuroimage 31:1650–1665). This study tested the hypothesis that, in amnesic MCI subjects, high amplitude of baseline cortical alpha rhythms is related to long‐term stability of global cognition on clinical follow‐up. Resting electroencephalographic (EEG) data were recorded in 100 amnesic MCI subjects during eyes‐closed condition. EEG rhythms of interest were delta (2–4 Hz), theta (4–8 Hz), alpha1 (8–10.5 Hz), alpha2 (10.5–13 Hz), beta1 (13–20 Hz), and beta2 (20–30 Hz). Cortical EEG sources were estimated by low‐resolution brain electromagnetic tomography (LORETA). Global cognition was indexed by mini mental state evaluation (MMSE) score at the time of EEG recordings (baseline) and about after 1 year. Based on the MMSE percentage difference between baseline and 1‐year follow‐up (MMSEvar), the MCI subjects were retrospectively divided into three arbitrary groups: DECREASED (MMSEvar ≤ −4%; N = 43), STABLE (MMSEvar ≈ 0; N = 27), and INCREASED (MMSEvar ≥ +4%; N = 30). Subjects' age, education, individual alpha frequency, gender, and MMSE scores were used as covariates for statistical analysis. Baseline posterior cortical sources of alpha 1 rhythms were higher in amplitude in the STABLE than in the DECREASED and INCREASED groups. These results suggest that preserved resting cortical neural synchronization at alpha frequency is related to a long‐term (1 year) stable cognitive function in MCI subjects. Future studies should use serial MMSE measurements to confirm and refine the present results. Hum Brain Mapp, 2011. © 2010 Wiley‐Liss, Inc.